Basic Assumptions of Human Science (Rationalism, Empiricism, Criticism, Intuitionism) for The Development of Science - Arief Rahman; Muhammad Zainal Abidin (STAIFAS-Press, 2023)
Knowledge is realized is something very valuable, and vice versa, ignorance is a bad thing in human life. However, most do not know in depth what they consider to be knowledge. This article discusses the basic assumptions of human science. First explained Rationalism, Empiricism, Criticism, and Intuitionism. The type of research used in this article is descriptive analytics, this article uses data collection techniques in the form of a literature study to collect data as the main source. This is followed by a description of the various basic assumptions.